2021
DOI: 10.3390/ijms222011246
|View full text |Cite
|
Sign up to set email alerts
|

AK-I-190, a New Catalytic Inhibitor of Topoisomerase II with Anti-Proliferative and Pro-Apoptotic Activity on Androgen-Negative Prostate Cancer Cells

Abstract: Castration-resistant prostate cancer (CRPC) is a clinical challenge in treatment because of its aggressive nature and resistance to androgen deprivation therapy. Topoisomerase II catalytic inhibitors have been suggested as a strategy to overcome these issues. We previously reported AK-I-190 as a novel topoisomerase II inhibitor. In this study, the mechanism of AK-I-190 was clarified using various types of spectroscopic and biological evaluations. AK-I-190 showed potent topoisomerase II inhibitory activity thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Cell cycle regulation plays a crucial role in malignant transformation and developing resistance to chemotherapy 42 . Several existing catalytic topoisomerase IIα inhibitors exhibit a different mechanism of cell cycle suppression than Topo II poisons 43 . Studies on cell cycle progression showed that among all compounds, 36a, along with signi cantly reduced cell proliferation induced G1 phase cell cycle arrest in almost all cancer cell lines tested, except for the U-2-OS, where we observed a time-dependent block in the G2/M.…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle regulation plays a crucial role in malignant transformation and developing resistance to chemotherapy 42 . Several existing catalytic topoisomerase IIα inhibitors exhibit a different mechanism of cell cycle suppression than Topo II poisons 43 . Studies on cell cycle progression showed that among all compounds, 36a, along with signi cantly reduced cell proliferation induced G1 phase cell cycle arrest in almost all cancer cell lines tested, except for the U-2-OS, where we observed a time-dependent block in the G2/M.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in drug resistance in leukemic cells in high-density cultures was marked earlier [ 50 , 51 ]; however, the mechanism of this phenomena remains unclear. The results of our work show the great increase in the resistance of different AML cells (lines HL-60, THP-1, MV411, U937) in high-density cultures to inhibitors of topoisomerases, etoposide and topotecan [ 52 , 53 ]; an antimetabolite, cytarabine [ 54 ]; DNA targeting antitumor drugs doxorubicin and cisplatin [ 55 , 56 , 57 ]; as well as to antitumor recombinant protein izTRAIL [ 58 ]. It was important that the increase in the drug resistance of AML cells in high-density cell culture was reversible and that the transfer of the AML cells from high-density to low-density cultures decreased the resistance to an initial state.…”
Section: Discussionmentioning
confidence: 99%
“…3 Several well-known (e.g., etoposide and doxorubicin) and newly developed TOP II inhibitors have demonstrated potential anti-CRPC activities in both in vitro studies and clinical trials. 3,[6][7][8][9] Notably, it has been reported that cabazitaxel-resistant CRPC cells show higher expression levels of TOP IIα protein than parent CRPC cells. Docetaxel-administered tissues and metastatic tumors also demonstrated higher TOP IIα expression levels.…”
Section: Introductionmentioning
confidence: 99%